Isolation and characterization of genomic clones covering the chicken vitellogenin gene. - Arnberg, A C (1981)
A series of overlapping recombinant clones, which cover the vitellogenin gene, has been isolated from a phage-lambda linked chicken gene library. The DNA of the overlapping clones spans 28 kb of contiguous DNA sequences in the chicken genome. Electron microscopic analysis of hybrids between vitellogenin mRNA and the genomic clones indicates that the chicken vitellogenin gene has a length of approximately 22 kb, about 3.8 times the size of the mRNA. The mRNA sequence is interrupted by at least 33 intervening sequences (introns). Comparison with the vitellogenin gene A2 from Xenopus laevis (Wahli et al., 1980, Cell 20: 107-117) indicates conservation of the number and length of the exons during evolution. Heteroduplex analysis reveals a short stretch of sequence homology between the genes from chicken and frog.